A genre-based study of moves analysis and layout in car print advertisements / Nurulain Abdullah - Nurulain, Abdullah (2014)
The increasing number of car sales in automotive industry has caused advertisers or companies to focus on more than just selling a car. The car companies or the advertisers need to differentiate themselves and create different strategies from other advertisers to promote/sell their cars. Therefore, it is interesting to examine how advertisers communicate or persuade the readers to buy a car. This study examines the move structure of car advertisements in a local newspaper which is The Star. This purpose of this study is to analyze the rhetorical structure and communicative purposes of car advertisements. This study adopted Kathpalia’s (1993) nine move structure as the framework to analyze the data collected. Kathpalia method of steps also are used in this study to strengthen the move analysis. In addition, this study also looks at the multimodality aspects of car advertisements, which in this case, is the layout of the advertisements. Forty-eight cars’ advertisements are collected and each move and layout found in each advertisement are identified and the frequency occurrence of each move is recorded in a table. The move that has a frequency occurrence of more than 50% is known as a prominent move. Out of nine moves from Kathpalia’s framework, only eight moves are prominent in this study. The moves are, headlines, urging action, justifying the product, establishing credentials, appraising the product, offering incentives, pressure tactics and targeting the market moves. There is only one move that is not prominent in this study which is the endorsements or testimonials move. Thus, it shows that Kathpalia’s nine move structure is useful/applicable for investigating the structure of car advertisements. Beside Kathpalia’s theoretical framework, this study also adopted Kress and van Leeuwen visual grammar theory to analyze the layout of car advertisements. The findings show that car advertisements tend to use a vertical layout rather than a horizontal layout. The layout found in car advertisements are closely related to the realization of different moves as the layout and moves can form a package that brings meanings to the advertisements. The different choices of moves and layout that are used by the advertisers brings to the final conclusion that the advertisers try to persuade the readers to buy the car.